ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Beatrix Apriani Kopong (2021)
This research is categorized as quantitative research. The goal is to find out & analyze the effect of each variable X (profitability, company size & debt policy) on variable Y (firm value) in issuers in the consumer goods industry listed on the IDX. The population of this research is consumer goods companies, amounting to 40 and the sample was taken based on the Slovin formula, which amounted to 36. The data analysis model is panel data regression and uses the help of the E-views 11 program. The results of data analysis are profitability with firm value has no effect, firm size and firm value have a negative effect and debt policy with firm value has a positive effect.